Determination of third-order nonlinear optical properties of ABI derivatives - Bundulis, Arturs; Rutkis, Martins (International Frequency Sensor Association, 2019)
In this paper we studied linear and nonlinear optical properties of novel organic materials MeSBI and MeOBI in form of solution with chloroform as solvent. For experimental measurements we implemented Z-scan method as it is one of the most widely used methods for nonlinear optical studies and can simultaneously measure two-photon absorption and Kerr effects. 1064 nm Nd:YAG laser with 30 ps pulse duration and 10 Hz repetition rate was used to avoid any thermal contribution to changes of optical properties and correctly evaluate magnitude of third-order nonlinear optical effects. Using acquired values we also calculated third-order susceptibility and second-order hyperpolarizability, as these coefficients are more appropriate for properties comparison on molecular level. Both materials possess insignificant absorption over 500 nm which makes them applicable for all-optical devices in infra-red spectrum. Acquired data for MeSBI and MeOBI were compared with data for previously studied ABI derivative DMABI to better understand how different structural configuration influence third-order nonlinear optical properties.
This material is based upon work supported by the ERDF 1.1.1.1 activity project Nr. 1.1.1.1/16/A/046 “Application assessment of novel organic materials by prototyping of photonic devices”.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Nonlinear optics; Kerr effect; Two-photon absorption; Organic materials; All-optical switching